The core of Francisco Suárez’s doctrine about resistance and tyrannicide - Oporto, Pablo Font (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This article tries to resume the exposition of Francisco Suárez about the problem of the resistance to the tyrant and its interpretation in the scientific doctrine. Suárez distinguishes betweentwo kinds of tyrants: the bad ruler and the usurper. The first only can be murdered in self-defense ofproper life or community; the second can be murdered by any person member of the community, on several conditions. Suárez is criticized because the only limits he establishes to political power are resistance and tyrannicide. However, these mean a democratic control really and physically possible inthe sociopolitical reality of his days.